Electrical and aging properties of doped barium titanate ceramics - Dechakupt T. (2014)
The tetragonal structured Ba(Ti1-xFex)O3 ceramics where x = 0, 0.005 and 0.01 were prepared by conventional mix-oxide method. Aging of dielectric properties and ferroelectric hysteresis loop was studied as a function of time. It was found that two aging stages might be existed in the aging process. The effect of Fe doping in barium titanate is not clearly seen in the aging of the dielectric properties while the effect obviously has influence on the P-E hysteresis loops. It is shown that the P-E loop of Fe doped compositions become constricted after aging. The remanent polarization and coercive field decreases as a function of time. The decreasing rate is higher for higher content of Fe dopant.